Remote Sensing of the Changing Oceans - Tang, DanLing; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
Remote Sensing of the Changing Oceans is a comprehensive account of the basic concepts, theories, methods and applications used in ocean satellite remote sensing. The book provides a synthesis of various new ideas and theories and discusses a series of key research topics in oceanic manifestation of global changes as viewed from space. A variety of research methods used in the analysis and modeling of global changes are introduced in detail along with numerous examples from around the world$1 (Bs oceans. The authors review the changing oceans at different levels, including Global and Regional Observations, Natural Hazards, Coastal Environment and related scientific issues, all from the unique perspective of Satellite Observation Systems. Thus, the book not only introduces the basics of the changing oceans, but also new developments in satellite remote sensing technology and international cooperation in this emerging field.s
Satellite Observation System and International Cooperation -- Global Changes -- Coastal Environment -- Regional Observation -- Natural Hazards.
Keywords: Geography; Climate change; Oceanography; Natural disasters; Coasts; Remote sensing; Geography; Remote Sensing/Photogrammetry.; Oceanography; Climate Change/Climate Change Impacts; Natural Hazards; Coastal Sciences; Climate Change; Electronic books